Paleomagnetic Constraints on the Duration of The Australia-Laurentia Connection in the Core of the Nuna Supercontinent - Kirscher, Uwe; Mitchell, Ross; Liu, Yebo; Nordsvan, Adam; Cox, Grant; Pisarevsky, Sergei; Wang, Chong; Wu, Lei; Murphy, J. Brendan; Li, Zheng-Xiang (GEOLOGICAL SOC AMER, INC, 2020)
The Australia-Laurentia connection in the Paleoproterozoic to Mesoproterozoic supercontinent Nuna is thought to have initiated by ca. 1.6 Ga when both continents were locked in a proto-SWEAT (southwestern U.S.–East Antarctic) configuration. However, the longevity of that configuration is poorly constrained. Here, we present a new high-quality paleomagnetic pole from the ca. 1.3 Ga Derim Derim sills of northern Australia that suggests Australia and Laurentia were in the same configuration at that time. This new paleopole also supports a connection between Australia and North China and, in conjunction with previously reported data from all continents, indicates that the breakup of Nuna largely occurred between ca. 1.3 and 1.2 Ga.